Moderating effect of price on the relationship of economic animosity and ethnocentrism with purchase decision of retail consumers of Jharkhand - Shandilya, Abhinav Kumar; Kumar, Dilip (Gyan Management Journal, 2023)
Multinational Companies (MNCs) are expanding their business to  maintain the growth rate. Many developing countries like India are  welcoming the MNCs to grab the benefits like foreign investment,  advanced technology, proper utilisation of natural resources,  employment etc., to name a few. MNCs like Nestle, CocaCola, Procter  and Gamble, Ranbaxy Laboratories, and Pepsico have spread their  business in India in food processing, beverage, consumer goods,  pharmaceuticals, and food and beverage. The products of these MNCs  are now challenged by Patanjali’s “Swadesi aur Sudh” products. This  study investigates the effects of economic animosity, ethnocentrism,  and price on consumers’ purchase decisions of the middle-aged  service class.
Keywords: Consumer goods; Economic animosity; Ethnocentrism; Price; Purchase decision; Swadesi